PENGEMBANGAN MODUL AJAR BERBASIS RADEC UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK KELAS IV SEKOLAH DASAR - Norma Andini, - (2023)
This study aims to describe the design development, the feasibility of a RADEC ( Read, Answer, Discuss, Explain, and Create ) based teaching module on science material in elementary schools in an effort to improve the creative thinking skills of fourth grade elementary school students. The background of this research is that there is still a low level of students' creative thinking skills in solving problems in learning. The research method used is Design and Development (D&D) proposed by Richey and Klein using the Planning, Production, Evaluation (PPE) research procedure. The teaching modules in this study were validated by three experts, namely material experts, media experts and learning experts. The results of the material expert validation get a percentage of 100% and are included in the very feasible criteria. The validation results from media experts get a percentage of 77.7% and are included in the feasible criteria. The results of the validation of learning experts get a percentage of 82.2% and get very decent criteria. In addition, the researchers conducted a limited trial of 10 students in class IV phase B of elementary school. Trials were conducted to test product legibility and limited trials to determine students' creative thinking skills. The results of limited trials conducted through the pretest and posttest obtained an average value of students' pretest results t is 32.5 while the average posttest result t is 82. It can be seen that the average value of posttest results is greater and significantly different from the pretest value ( 32.5 > 82)